Distribuição de raízes e a relação com o estado hídrico de laranjeira 'valência' enxertada sobre limoeiro 'cravo' - Adriano, Elisa [UNESP] (2015)
Among the factors related to the development and production of citrus water availability is one of the most relevant. The use of irrigation in citrus orchards have been great increase and this demand creates the need for studies involving the water status of plants and all processes related to water use. The objective was to study the root distribution of 'Valencia' orane grafted on 'Rangpur' lime and the maximum depth in irrigated and rainfed system in sandy soil and the relationship between the distribution of the roots and the water status of plants. The study was conducted in a commercial orchard in the city of Itatinga / SP. The experimental design was a randomized block, consisting of two treatments (irrigated and rainfed) and four replications. The root of the orange system was evaluated and the maximum depth through soil samples with motorized auger, estimating the mass and area of roots. The increase of biomass was estimated by biomass measurements, root biomass and fruit production. The water status of plants was monitored by means of sap flow sensors, monthly reviews of the bottom leaf potential and minimum leaf potential, monthly reviews of gas exchange and stomatal conductance. The total biomass of fine roots and the maximum depth of rooting were higher in rainfed than in irrigated. The aplication of water, equivalent to 3% - 15% of annual rainfall, depending on the study year, reduced to 14% biomass of fine roots regarding the rainfed treatment and decreased 1 m maximum depth of rooting. The mass density of fine roots was between 536 g m-2 in the irrigated treatment during the dry season of 2012 and 1210 g m-2 in the rainfed treatment during the rainy season of 2014. The maximum depth of the root system was 6.5 m in irrigated treatment and ...